PENGARUH PROMOSI, STORE ATMOSPHERE, DAN VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Meilaty Finthariasari; Sri Ekowati; Erwin Febriansyah ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2020)
This research aims to determine the effect of store atmosphere, promotions, and product variations on purchasing decisions (case study of Kampung Kecil Restaurant of Bengkulu City). The problem in this study was whether the store atmosphere, promotions, and product variations affect the purchasing decisions. There were 80 respondents as the samples taken by accident (accidental sampling). The data was collected by using the questionnaire. The analysis techniques used were multiple linear regression, coefficient of determination, and hypothesis testing. Based on the results of this research, it can be seen that the store atmosphere had a significant effect on the purchasing decision of the consumers in the Kampung Kecil restaurant because a significant value of 0.046 was lower than 0.05. The promotion had a significant effect on the purchasing decision of the consumers because a significant value of 0.015 was lower than 0.05. The Product variations also had a significant effect on the consumer of purchasing decision because a significant value of 0.00 was lower than 0.05. The coefficient of determination of R square was 0.721. It meant that the purchasing decision can be explained 72.1% by the independent variables namely the store atmosphere, promotion, and product variations. While the rest (100-72.1% = 27.9%) is affected by other factors that are not examined in this research. Keywords: Store Atmosphere, Promotions, Product Variations, and Purchasing Decisions